2019
DOI: 10.1002/jcla.23125
|View full text |Cite
|
Sign up to set email alerts
|

Association between the miRNA‐149 rs2292832 T>C polymorphism and Kawasaki disease susceptibility in a southern Chinese population

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: Kawasaki disease (KD), which is characterized by vasculitis, is prone to occur in patients under 5 years of age, has an ambiguous etiology, and displays coronary artery lesions as the chief complication. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The miR-146a “rs57095329” variant was associated with increased SLE risk in East Asian regions [ 74 , 79 , 80 ]. The miR-149 rs2292832 polymorphism may confer susceptibility to Kawasaki disease [ 81 ], allergic rhinitis, and comorbid asthma in Chinese children [ 82 ]. The association of the miRNA-34a rs2666433 variant with SLE susceptibility and the miR-17 rs4284505 variant with susceptibility and severity of SLE were also evident in the present cohort [ 2 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The miR-146a “rs57095329” variant was associated with increased SLE risk in East Asian regions [ 74 , 79 , 80 ]. The miR-149 rs2292832 polymorphism may confer susceptibility to Kawasaki disease [ 81 ], allergic rhinitis, and comorbid asthma in Chinese children [ 82 ]. The association of the miRNA-34a rs2666433 variant with SLE susceptibility and the miR-17 rs4284505 variant with susceptibility and severity of SLE were also evident in the present cohort [ 2 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rs2292832 T>C mutation of miR-149 may affect its expression and susceptibility to disease [40,63]. miR-149 is a proapoptotic miRNA that affects the expression of the Akt1 15 Disease Markers and E2F1 gene, which has been shown to promote cell growth and cell cycle progression in IBD-associated colorectal cancer [120].…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant correlation was revealed, the subgroup analysis showed that the rs1625579 T>G polymorphism of miRNA-137 increased the risk of KD in southern Chinese children aged<12 months. Later, several one-center studies demonstrated that the miR-218 rs11134627 A>G, miR-146a rs2910164 C>G, miR-196a2 rs11614913 T >C, miRNA-149 rs2292832 T >C polymorphisms are not associated with the susceptibility of Kawasaki disease ( 64 67 ). However, these results still need to be confirmed in a multi-center study involving of larger sample.…”
Section: The Inherent Mechanism Of Mirnas In Kawasaki Diseasementioning
confidence: 99%